Mycobacterium tuberculosis RipA Dampens TLR4-Mediated Host Protective Response Using a Multi-Pronged Approach Involving Autophagy, Apoptosis, Metabolic Repurposing, and Immune Modulation - Shariq, Mohd; Quadir, Neha; Sharma, Neha; Singh, Jasdeep; Sheikh, Javaid A.; Khubaib, Mohd; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Immunology, 2021)
Reductive evolution has endowed Mycobacterium tuberculosis (M. tb) with moonlighting in protein functions. We demonstrate that RipA (Rv1477), a peptidoglycan hydrolase, activates the NFκB signaling pathway and elicits the production of pro-inflammatory cytokines, TNF-α, IL-6, and IL-12, through the activation of an innate immune-receptor, toll-like receptor (TLR)4. RipA also induces an enhanced expression of macrophage activation markers MHC-II, CD80, and CD86, suggestive of M1 polarization. RipA harbors LC3 (Microtubule-associated protein 1A/1B-light chain 3) motifs known to be involved in autophagy regulation and indeed alters the levels of autophagy markers LC3BII and P62/SQSTM1 (Sequestosome-1), along with an increase in the ratio of P62/Beclin1, a hallmark of autophagy inhibition. The use of pharmacological agents, rapamycin and bafilomycin A1, reveals that RipA activates PI3K-AKT-mTORC1 signaling cascade that ultimately culminates in the inhibition of autophagy initiating kinase ULK1 (Unc-51 like autophagy activating kinase). This inhibition of autophagy translates into efficient intracellular survival, within macrophages, of recombinant Mycobacterium smegmatis expressing M. tb RipA. RipA, which also localizes into mitochondria, inhibits the production of oxidative phosphorylation enzymes to promote a Warburg-like phenotype in macrophages that favors bacterial replication. Furthermore, RipA also inhibited caspase-dependent programed cell death in macrophages, thus hindering an efficient innate antibacterial response. Collectively, our results highlight the role of an endopeptidase to create a permissive replication niche in host cells by inducing the repression of autophagy and apoptosis, along with metabolic reprogramming, and pointing to the role of RipA in disease pathogenesis.